Colombian Foreign Policy and Public Opinion in Electoral Campaigns: Política exterior colombiana y opinión pública en campañas electorales - Sánchez, Fabio; Cardozo, Alejandro (Araucaria, 2024)
What is the relationship between foreign policy, electoral campaigns, and public opinion? This work analyzes the electoral campaigns in Colombia in 2018 (Iván Duque) and 2022 (Gustavo Petro). The profiles of the candidates and their programmatic agendas are analyzed, identifying the continuity of issues associated with peace, security, borders, and the complex relationship with Venezuela. Despite the above, there was a turn to the left that shows changes in the preferences of Colombian public opinion.